PENGARUH BAURAN KOMUNIKASI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK TOYOTA DI KOTA MALANG (Studi Pada Konsumen Dealer AUTO2000 Sutoyo) - Sugiarti, Fita Febri (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study analyze the influence of the marketing communications mix to the purchasing decision of Toyota products in Malang. The independent variables in this study consists of advertising , sales promotion , events and experiences , direct marketing , interactive marketing , word of mouth marketing and personal selling , while the dependent variable purchase decision . The results of the analysis conducted in this study have met the test requirements of multiple linear regression analysis. Data were collected through questionnaires distributed to 80 respondents in Dealer AUTO2000 Sutoyo. This study has been tested for validity and reliability so that it can continue to test the classical assumption of normality test, non heteroskesdasitas assumption, and the assumption of non multikolenieritas test. After the classical assumption test done, then followed by the multiple regression analysis to determine the effect of independent variables on the dependent variable and followed by testing the hypothesis by performing the F test, t test and dominant test. Keywords : advertising , sales promotion , events and experiences , direct marketing , interactive marketing , word of mouth marketing and personal selling, purchase decision.